Epigenetic changes in hypothalamic appetite regulatory genes may underlie the developmental programming for obesity in rat neonates subjected to a high-carbohydrate dietary modification. (24th June 2013) - Mahmood, S.; Smiraglia, D. J.; Srinivasan, M.; Patel, M. S.
Abstract : Earlier, we showed that rearing of newborn rats on a high-carbohydrate (HC) milk formula resulted in the onset of hyperinsulinemia, its persistence in the post-weaning period and adult-onset obesity. DNA methylation of CpG dinucleotides in the proximal promoter region and modifications in the N-terminal tail of histone 3 associated with the neuropeptide Y ( Npy ) and pro-opiomelanocortin ( Pomc ) genes were investigated to decipher the molecular mechanisms supporting the development of obesity in HC females. Although there were no differences in the methylation status of CpG dinucleotides in the proximal promoter region of the Pomc gene, altered methylation of specific CpG dinucleotides proximal to the transcription start site was observed for the Npy gene in the hypothalami of 16- and 100-day-old HC rats compared with their methylation status in mother-fed (MF) rats. Investigation of histone tail modifications on hypothalamic chromatin extracts from 16-day-old rats indicated decreased acetylation of lysine 9 in histone 3 (H3K9) for the Pomc gene and increased acetylation for the same residue for the Npy gene, without changes in histone methylation (H3K9) in both genes in HC rats. These findings are consistent with the changes in the levels of Npy and Pomc mRNAs in the hypothalami of HC rats compared with MF animals. Our results suggest that epigenetic modifications could contribute to the altered gene expression of the Npy and Pomc genes in the hypothalami of HC rats and could be a mechanism leading to hyperphagia and the development of obesity in adult female HC rats.